Pengaruh Informasi Asimetrik Terhadap Masalah Agency Kontraktual dalam Pembiayaan Mudharabah - Nur Fauziah; Nur Syakdiyyah (Jurnal Aplikasi Bisnis, 2017)
This study analyzed the influence of Asymmetric Infonnation of the Contractual Agenty Problems in Mudharahah. Asymmetric information in this study was based on the form of adverse selection and moral hazard. Moral hazard is an aberration that cannot be observed by Shahibul Maal. Negative actions or activities of the entrepreneur (mudharib) are not known by Shahibul Maal so that mudharib can freely act without the knowledge of them. Adverse selection associated with the ethics of a mudharib in herently and cannot be known certainly by Shahibul Maal.The research was conducted on Sharia Commercial Banks in DIY and Central Java, namely BTN Syariah, Bank Syariah Mandiri, BRI Syariah. Through regression analysis, it showed that Moral Hazard and Adverse Selection effected on the contractual agency problems both individually and simultanously.